Epidural myelolipoma in a Silken Windhound. (14th March 2022) - Ierardi, Rosalie A.; Anderson, Melanie N.; Bryan, Jeffrey N.; Matheson, Jodi S.; Sample, Saundra H.; Coates, Joan R.
Abstract: A 12‐year‐old female spayed, Silken Windhound dog was presented with a 3‐month history of lethargy and cervical and lumbosacral spinal pain. No significant abnormalities were noted on CBC or serum biochemical assays. Magnetic resonance imaging of the spine demonstrated a soft tissue mass within the ventral and right epidural space at the level of the L7 vertebra. During surgery, a pale brown mass was identified within the epidural fat. Cytologic and histopathologic examinations demonstrated that the mass was composed of adipose tissue and hematopoietic elements, consistent with a myelolipoma. The lumbosacral spinal pain resolved after surgery. Epidural myelolipomas are rarely reported in the human and veterinary literature.